Identification of seminal markers of male accessory gland inflammation: From molecules to proteome. (10th July 2018) - Grande, Giuseppe; Milardi, Domenico; Baroni, Silvia; Luca, Giovanni; Pontecorvi, Alfredo
Abstract : Male accessory gland infection/inflammation (MAGI) is a frequent disease, mostly with a chronic course, involving 1 or more sexual accessory glands. Majority of the MAGIs remain asymptomatic, thereby leading to a dilemma whether to treat these patients or not. It is moreover noteworthy that the diagnosis of MAGI is difficult, since patients are frequently asymptomatic and semen samples or prostatic secretions are often free from bacteria. As a consequence the identification of novel and reliable markers of inflammation in seminal plasma is an open challenge. If leukocytospermia and polymorphonuclear elastase and the analysis of the secretory products of male accessory glands have been widely used in the past, their diagnostic significance is discussed. Some cytokines (IL‐6 and IL‐8) and protein markers (suPAR) have been reported in the last years as the most promising markers for the diagnosis and the follow‐up of MAGI. Recent advances in proteomic techniques undoubtedly represent a real promise in the future for the identification of novel markers of MAGI. This article provides an overview of key seminal biomarkers of MAGI, including the novel perspectives of the putative markers deriving by the most recent proteomic approaches.